Respuesta :

Answer:

[tex]\huge \boxed{a = 2b + 6c}[/tex]

Step-by-step explanation:

b = 1/2a - 3c

Add 3c to both sides of the equation.

b + 3c = 1/2a - 3c + 3c

b + 3c = 1/2a

Switch sides.

1/2a = b + 3c

Multiply both sides of the equation by 2.

2(1/2a) = 2(b + 3c)

a = 2b + 6c

Step-by-step explanation:

[tex]b = \frac{1}{2} a- 3c[/tex]

Multiply both sides ✖ of the equation by 2

[tex]2b = a - 6c[/tex]

Move the variable to the left-hand side and change its sign

[tex] - a + 2b = - 6c[/tex]

MOVE THE VARIABLE TO THE RIGHT-HAND SIDE AND CHANGE ITS SIGN

[tex] - a = - 6c - 2b[/tex]

Change the sign on both sides of the equation

[tex]a = 6c + 2b[/tex]

Therefore the answer is

[tex]a = 6c + 2b[/tex]